PENGARUH BUDAYA ORGANISASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PT. PERTAMINA PATRA NIAGA FUNGSI RETAIL SALES JAWA BAGIAN BARAT - Defri Maulana Ibrahim; Amilia Hasbullah, S.IP., M.Sc. (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2022)
Purpose to analyze the influence of organizational culture and work environment on employee performance PT. Pertamina Patra Niaga Fungsi Retail Sales Jawa Bagian Barat. This research is included in the category of causal associative research using a quantitative approach. The research was conducted by distributing questionnaires to 30 respondents, all of whom were employees of Pertamina Patra Niaga Fungsi Retail Sales Jawa Bagian Barat. The research method using partially and simultaneous linear regression analysis. The results of the study indicate that collectively or individually, organizational culture and work environment have a positive and significant effect on employee performance.